Pengembangan Media Diorama Siklus Air Untuk Pembelajaran IPA Kelas IV SD - Subhi, Muhammad; Solbia; Herlina, Tri Linda; Caramoy, Ajeng (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This research focuses on creating a water cycle diorama as an instructional medium for Natural Science education among fourth-grade students at SD Negeri 222 Palembang. The study employs a Research and Development (R&D) methodology following the ADDIE framework, which encompasses five sequential phases: Analysis, Design, Development, Implementation, and Evaluation. Following the development phase, the instructional medium underwent comprehensive validation by subject matter specialists and educational media experts to determine its suitability. Additionally, empirical trials involving educators and students were conducted to examine the medium's practicality and pedagogical effectiveness. Expert validation demonstrated exceptional validity, with subject matter specialists rating the medium at 86% and educational media experts providing an 87% validation score. Practicality assessment conducted by classroom practitioners yielded a 92% rating, confirming the medium's high usability in educational settings. Student trials were implemented through three progressive phases: individual assessment achieving 98% practicality, small group evaluation reaching 99%, and comprehensive field testing with 30 participants demonstrating 97% effectiveness. The findings indicate that the water cycle diorama serves as a highly suitable, practical, and pedagogically effective instructional tool for elementary science education at the fourth-grade level.